Direct and indirect inhibition of the circadian clock protein Per1: effects on ENaC and blood pressure - Alli, Abdel (Am J Physiol Renal Physiol, 2019)
Circadian rhythms govern physiological functions and are important for overall health. The molecular circadian clock comprises several transcription factors that mediate circadian control of physiological function, in part, by regulating gene expression in a tissue-specific manner. These connections are well established, but the underlying mechanisms are incompletely understood. The overall goal of this study was to examine the connection among the circadian clock protein Period 1 (Per1), epithelial Na(+) channel (ENaC), and blood pressure (BP) using a multipronged approach. Using global Per1 knockout mice on a 129/sv background in combination with a high-salt diet plus mineralocorticoid treatment, we demonstrated that loss of Per1 in this setting is associated with protection from hypertension. Next, we used the ENaC inhibitor benzamil to demonstrate a role for ENaC in BP regulation and urinary Na(+) excretion in 129/sv mice. We targeted Per1 indirectly using pharmacological inhibition of Per1 nuclear entry in vivo to demonstrate altered expression of known Per1 target genes as well as a BP-lowering effect in 129/sv mice. Finally, we directly inhibited Per1 via genetic knockdown in amphibian distal nephron cells to demonstrate, for the first time, that reduced Per1 expression is associated with decreased ENaC activity at the single channel level.